In Search of the Thermo/Halochromism of the Et(30) Pyridinium-N-Phenolate Betaine Dye - Caroli-Rezende, M; Aracena-Astudillo, A; Aracena-Astudillo, A (2012)
The thermohalochromic behavior of Reichardt s ET(30) betaine - the temperature-dependent variation of its halochromic band in the presence of a cation - was investigated for the first time in NaI solutions of HBD- (methanol, ethanol, 1-propanol, 1-butanol) and non-HBD-solvents (acetonitrile, dimethylformamide) at 15 and 55 °C. The solvent-dependent thermohalochromism of the pyridinium-N-phenolate betaine dye was interpreted in terms of the effect of the temperature on the dye-cation association in solution. © 2012 Elsevier B.V. All rights reserved.